Preliminary list of speakers for the Sperry Univac Symposium on Computers in Education and Research - Hawkins, Richard (NIL, 1981)
Prof Diraja Ungku Aziz was given a list of speakers who are attending the symposium. The topics will be confirmed later but speaker list is defined